The effects of core stability exercise on the dynamic balance of volleyball players - Sadeghi, H.; Shariat, A.; Asadmanesh, E.; Mosavat, M. (International Journal of Applied Exercise Physiology, 2013)
Dynamic balance is a key component of injury prevention and rehabilitation in sports. Training the core muscles has been hypothesized as an intervention for improving balance. However, there is a lack of current scientific evidence to support this claim. The purpose of this study was to evaluate the effects of a core stability program on dynamic balance of volleyball players as measured with the Star Excursion Balance Test (SEBT). Thirty healthy participants were divided into 2 groups: control and exercise groups. All participants performed the SEBT before and after 8-week exercise time. During the 8-week time, the exercise group performed a core stability program, whereas the control group abstained from any new exercise. These results also illustrated there was significant differences in the scores for pre-test and post-test of all direction according SEBT in the experimental group. An independent sample t-test was conducted to compare experimental and control group (F=43.573, Sig=0.000). These results were a significant difference in the scores for control and experimental groups. Maximum excursion distances improved for the exercise group, compared with the control group. This result justifies the hypothesis that core strengthening can improve dynamic postural control during landing of volleyball players significantly.